Analytical solutions of the fifth-order time fractional nonlinear evolution equations by the unified method - Majeed, Abdul; Rafiq, Muhammad Naveed; Kamran, Mohsin; Abbas, Muhammad; İnç, Mustafa (World Scientific Publ Co Pte Ltd, 2022)
This key purpose of this study is to investigate soliton solution of the fifth-order Sawada-Kotera and Caudrey-Dodd-Gibbon equations in the sense of time fractional local M-derivatives. This important goal is achieved by employing the unified method. As a result, a number of dark and rational soliton solutions to the nonlinear model are retrieved. Some of the achieved solutions are illustrated graphically in order to fully understand their physical behavior. The results demonstrate that the presented approach is more effective in solving issues in mathematical physics and other fields.
Keywords: Local M-derivative; the fifth-order Sawada-Kotera and Caudrey-Dodd-Gibbon equations; the unified method; dark and rational solitons